Dispositivos de vida pública: revisitando teorias e procedimentos de avaliação dos espaços públicos - Bandeira, Ângelica Carvalho (2017)
This dissertation has as objective define the variables for the evaluation of public life in Brazilian public spaces that can be applied with citizen participation in the future, resulting in guidelines for action. In this way, we intend to fill the existing gap in the design practice of the field of Architecture and Urbanism, which does not incorporate the citizen in the whole process and which proposes a fragmented analysis of public life. From a bibliographical research, the first part of the study is dedicated to the conceptual body that guided the development of the research, the second contains the sample of the procedures of analysis of public spaces traveled by the analogy of the itinerary, that is, showing how to evaluate and one minimum series of paths, or dimensions, by which the evaluation of public life can be carried out. From this theoretical-methodological referential arised the Public Life Devices that allow the evaluation of public spaces with citizen participation from phases and categories that, in turn, gathering criteria and registration techniques. Against the study can be concluded first that the theories on public life and public space are, , as a rule, contrasting with the Brazilian reality, but this could be changed through citizen participation. In a second moment, it is verified that every project implies in unforeseeable deviations, so, the specialists can’t order and control the experience in a space. But on the other hand this does not constitute negatively and yes portrays the public life itself. It is also considered that the public life notion is not just constituted in using the public space besides the circulation, but in claim the character political, social, affectionate and cognitive in the relationship people/citizen/subject-lived space/ existence. Finally, it is understood that citizen participation is necessary to attend to the aspirations of the population, especially those of the most excluded, besides implying in the full exercise of democracy.